2003
DOI: 10.1080/0962935031000114943
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory actions of acupuncture

Abstract: Acupuncture has a beneficial effect when treating many diseases and painful conditions, and therefore is thought to be useful as a complementary therapy or to replace generally accepted pharmacological intervention. The attributive effect of acupuncture has been investigated in inflammatory diseases, including asthma, rhinitis, inflammatory bowel disease, rheumatoid arthritis, epicondylitis, complex regional pain syndrome type 1 and vasculitis. Large randomised trials demonstrating the immediate and sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
195
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(206 citation statements)
references
References 103 publications
1
195
0
10
Order By: Relevance
“…Acupuncture, a therapeutic modality with few or no adverse effects, has been used in China and other Asian countries for thousands of years to treat a variety of conditions, including inflammatory disease [5,6]. Clinical trials show that electroacupuncture (EA) has beneficial effects in patients with various inflammatory diseases [7]. A recent clinical trial reported that EA significantly alleviated the symptoms of patients with knee osteoarthritis (OA) compared to sham acupuncture control during a long follow-up period of 26 weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, a therapeutic modality with few or no adverse effects, has been used in China and other Asian countries for thousands of years to treat a variety of conditions, including inflammatory disease [5,6]. Clinical trials show that electroacupuncture (EA) has beneficial effects in patients with various inflammatory diseases [7]. A recent clinical trial reported that EA significantly alleviated the symptoms of patients with knee osteoarthritis (OA) compared to sham acupuncture control during a long follow-up period of 26 weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…A review article by Zijlstra et al 21 suggested a hypothesis for the anti-inflammatory action of acupuncture. According to the authors, the insertion of acupuncture needles stimulates release of b-endorphins (calcitonin gene-related peptide [CGRP] and substance P).…”
Section: Anti-inflammatory Actionmentioning
confidence: 99%
“…There are several mechanisms through which acupuncture believes to affect the neurophysiology and pain pathways. These include stimulation of nerves and muscles with subsequent release of endorphins and other neurohumoral factors affecting the pain pathways in brain and spinal cord [10,11], anti-inflammatory effects through release of immunomodulatory and vascular factors [12]; by increasing neuropeptide Y [13] or endorphin levels [14]. It is suggested that acupuncture might work through variable combination of peripheral and central mechanisms along with psychological (placebo) effects [15].…”
Section: Acupuncture In Primary Headache Disorders; the Evidencementioning
confidence: 99%